2000
DOI: 10.1056/nejm200007063430101
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Risk of High-Order Multiple Pregnancy after Ovarian Stimulation with Gonadotropins

Abstract: Gonadotropin stimulation that is less intensive than is currently customary may reduce the incidence of high-order multiple pregnancy in infertile women, though only to a limited extent and at the expense of overall pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
2
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(123 citation statements)
references
References 14 publications
8
108
2
5
Order By: Relevance
“…21 If starting doses and incremental dose adjustments are not carefully titrated, ovulation induction or intra-uterine insemination protocols with gonadotrophins may lead to high rates of multifollicular growth. 22 Even with low-dose FSH stimulation, obese and insulin-resistant women with PCOS have a much greater tendency to develop a multifollicular response and, thus, a relatively high cycle cancellation rate in order to avoid hyperstimulation. 23 Balen and Jacobs 20 showed that, if a low-dose step-up regimen is used, it is necessary to decide on both the starting dose and the incremental dose, and starting doses ranging from 37.5 to 150 IU/day have been used.…”
Section: Ovarian Stimulation In Obese and Non-obese Pcosmentioning
confidence: 99%
“…21 If starting doses and incremental dose adjustments are not carefully titrated, ovulation induction or intra-uterine insemination protocols with gonadotrophins may lead to high rates of multifollicular growth. 22 Even with low-dose FSH stimulation, obese and insulin-resistant women with PCOS have a much greater tendency to develop a multifollicular response and, thus, a relatively high cycle cancellation rate in order to avoid hyperstimulation. 23 Balen and Jacobs 20 showed that, if a low-dose step-up regimen is used, it is necessary to decide on both the starting dose and the incremental dose, and starting doses ranging from 37.5 to 150 IU/day have been used.…”
Section: Ovarian Stimulation In Obese and Non-obese Pcosmentioning
confidence: 99%
“…In a review of their clinical practice Gleicher et al (2000) reported on pregnancy after COH.IUI in 3137 completed cycles. They reported a 14% clinical intrauterine pregnancy rate of which 71% were singletons, 22% twins, 5% triplets, 2.3% quadruplets, 1.1% quintuplets and 2% sextuplets.…”
Section: Controlled Ovarian Hyperstimulation: Intrauterine Inseminatimentioning
confidence: 99%
“…Studies have shown that super ovulation is associated with a twenty percent incidence of twin pregnancy and about ten percent incidence for higher order multiple pregnancy (10,11). Complications to both mother and foetuses are known to be significantly more with multiple pregnancies than singleton pregnancy.…”
Section: Introductionmentioning
confidence: 99%